Experimental investigation on heat transfer and hydrodynamic performance of nanofluids in forced convection - Tan, Brandon Ming Huang (Nanyang Technological University, 2020)
In recent years, research on nanofluids, which are fluids with particles containing small particles that are less than 100 nanometres in diameter, have seen anomalous thermal enhancement properties. With increased thermal properties, nanofluids have been considered to have relevant use in several industries, including electronics and nuclear reactors. One of the main obstacles to the industrial use of nanofluids, however, is the lack of understanding behind the mechanism for the increased heat transfer performance in these fluids. This research investigates the use of nanofluids containing graphitic carbon nanoparticles. These nanoparticles are found in the waste product from the purification of single-wall carbon nanotubes (SWCNT), and have been recycled into a nanofluid, with distilled water as the base fluid. It explores the potential and capability of the thermal and hydrodynamic properties of this nanofluid under forced convection. This research focuses on the forced convective heat transfer coefficient, heat transfer rate and pressure drop properties of this nanofluid. The nanofluids were tested over a range of water bath temperatures, from 40⁰C to 80⁰C, over a range of flow rates, from 0.4 litres per minute (0.4L/min) to 2.0 litres per minute (2.0L/min). Three nanofluids were used, with varying compositions. The first nanofluid, named nanofluid A, contains 0.01% weight of graphitic carbon nanoparticles, with dimethylformamide (DMF), another waste product from the purification of single wall carbon nanotubes. The second nanofluid, nanofluid B, also contains 0.01% weight of graphitic carbon nanoparticles with the surfactant sodium dodecyl sulfate (SDS) used. The third and last nanofluid, Nanofluid C has half the concentration of nanofluid B. Through this research, it has been discovered that such nanofluids containing graphitic carbon nanoparticles have heat transfer enhancement capabilities. The nanofluids containing SDS surfactant showed significant increases in the thermal properties. Nanofluid C, in particular, showed up to 80% improvement in the forced convective heat transfer coefficient. Nanofluid A showed limited thermal enhancement properties whereas Nanofluid B was slightly more effective, showing up to 5 to 10% increase in the thermal performance over water. Factors such as aggregation and amount of additives added to each nanofluid were discovered to have a great impact on the thermal enhancement properties of nanofluids. The 3 nanofluids investigated showed increased pressure drops with increasing flow rates when compared to water, hence suggesting that more pumping power could be required to maintain higher volumetric flow rates for these nanofluids. The results of the research show that there is untapped potential in nanofluids containing graphitic carbon nanoparticles and future research on different parameters, including concentration of nanoparticles, addition of additives and nanofluid temperature can also be conducted to establish further heat transfer and hydrodynamic properties of these nanofluids.